2019
DOI: 10.1002/fsn3.951
|View full text |Cite
|
Sign up to set email alerts
|

Functional characteristics and microbiological viability of foam‐mat dried Bambara groundnut (Vigna subterranea) yogurt from reconstituted Bambara groundnut milk powder

Abstract: Yogurt is a milk product produced from fermentation of milk sugars into lactic acid by the addition of yogurt starter culture containing Streptococcus thermophilus and Lactobacillus delbrueckii ssp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…These solubility values were lower compared to the WSI reported for freeze-dried yoghurt powder containing free Lactobacillus plantarum and probiotic fruit juice powders (Jouki et al, 2021 andDias et al, 2018). Notably, the postbiotic powders analyzed in this study displayed predominantly porous surfaces, which have been documented to enhance solubility when food powders are reconstituted (Hardy & Jideani, 2020). Swelling power and WSI are critical parameters for characterizing the rehydration properties of powders.…”
Section: Rehydration Characterization Of Postbiotic Powderscontrasting
confidence: 60%
“…These solubility values were lower compared to the WSI reported for freeze-dried yoghurt powder containing free Lactobacillus plantarum and probiotic fruit juice powders (Jouki et al, 2021 andDias et al, 2018). Notably, the postbiotic powders analyzed in this study displayed predominantly porous surfaces, which have been documented to enhance solubility when food powders are reconstituted (Hardy & Jideani, 2020). Swelling power and WSI are critical parameters for characterizing the rehydration properties of powders.…”
Section: Rehydration Characterization Of Postbiotic Powderscontrasting
confidence: 60%
“…Cooked bananas can be serves as a weaning diet for children, and their nutritional value can be improved by adding Bambara flour [68]. Recent studies on various food processing enterprises have shown that Bambara groundnut can be incorporated into their commodities [67,69]. The Center for Feature Crop (CFC) disclosed strategies for substituting other ingredients into Bambara groundnut recipes [11].…”
Section: Health and Medicinal Significance Of Bambara Groundnutmentioning
confidence: 99%
“…This is due to its unique appealing flavour, taste and light colour [52]. In fact, it has been suggested as a suitable weaning food due to its rich nutritional content [53].…”
Section: Repurposing Of Bambara Nutsmentioning
confidence: 99%